2020
DOI: 10.1159/000507784
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Related Glomerulopathy: A Latent Change in Obesity Requiring More Attention

Abstract: Background: Obesity has become a major public health problem, and the prevalence of kidney diseases has increased in parallel. Among kidney diseases caused by metabolic disorders, obesity-related glomerulopathy (ORG) is secondary to obesity. Summary: ORG is mainly caused by glomerular hyperfiltration, dysregulation of hormone and cytokine secretion in adipose tissues, and ectopic lipid accumulation in renal cells. ORG is pathologically characterized by glomerular hypertrophy, with or without focal and segmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 80 publications
1
28
0
4
Order By: Relevance
“…The increased sympathetic activation in obesity stimulates the renin-angiotensin system, resulting in insulin resistance (30). Insulin resistance resulting from insulin signaling interfering subsequently induces podocyte apoptosis, hypertrophy of the remaining podocytes, and glomerulosclerosis (31). In our study, reduced ADH1 was observed in genetically obese db/db mice.…”
Section: Discussionsupporting
confidence: 52%
“…The increased sympathetic activation in obesity stimulates the renin-angiotensin system, resulting in insulin resistance (30). Insulin resistance resulting from insulin signaling interfering subsequently induces podocyte apoptosis, hypertrophy of the remaining podocytes, and glomerulosclerosis (31). In our study, reduced ADH1 was observed in genetically obese db/db mice.…”
Section: Discussionsupporting
confidence: 52%
“…While TNF-alpha plays a fundamental role in progression of renal fibrosis, the increase in intracellular lipids has a nephrotoxic effect (culminating in glomerulosclerosis), compromising the structure and functioning of mitochondria, which contributes to progression of kidney disease. 87 Increased insulin production and insulin resistance contribute to mesangial expansion and renal fibrosis, and the observed activation of the renin-angiotensin-aldosterone system, since the vasoconstrictor effect of angiotensin II on renal arterioles leads to increased production of endothelin-1, stimulating proliferation of mesangial matrix, sodium retention, and vasoconstriction of renal arterioles. 88 Coronavirus can cause acute kidney damage in up to 15% of cases, which contributes to mortality.…”
Section: Pathophysiology Of Obesity and Its Relationship With Covid-1mentioning
confidence: 99%
“…The limited presence of full nephrotic syndrome in patients with ORG can be clinically significant since a progressive increase in proteinuria may go unnoticed for years, leading to late diagnosis of renal failure (29) . Many studies suggest that obesity-associated insulin resistance increases the risk of CKD progression following a period of "silent" glomerular hyperfiltration (31,32) . Obesity is significantly related to the development and progression of renal diseases other than ORG (29, A c c e p t e d A r t i c l e [33][34][35][36][37][38] .…”
Section: The Adverse Effects Of Obesity On Renal Outcomesmentioning
confidence: 99%